2011
DOI: 10.1111/j.1365-2486.2011.02500.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of nitrogen and microbial residues during 2000 years of rice paddy and non-paddy soil development in the Yangtze River Delta, China

Abstract: Lowland rice paddy soils may accumulate significant amounts of organic matter. Our aim was to investigate the role of prolonged paddy management on the nitrogen (N) status of the soils, and to elucidate the contribution of bacteria and fungi to long-term N accumulation processes. For this purpose, we sampled a chronosequence of 0-2000 years of rice cropping with adjacent non-paddy systems in the Bay of Hangzhou, China. The samples were analyzed for bulk density, total, mineral and microbial N (N mic ), and ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 64 publications
5
50
1
1
Order By: Relevance
“…Prior studies showed that the total content of soil amino sugar‐N in most instances significantly exceeded the total amount of soil microbial biomass‐N (Appuhn & Joergensen, ; Joergensen, ; Joergensen, Mäder, & Fließbach, ). In a chronosequence of prolonged rice paddy management, the concentration of nitrogen in soil amino sugars exceeded the nitrogen content in living biomass by a factor of 2 in plots with continuous cultivation of over 190–2,000 years (Roth et al, ). The constancy of this factor over such a long period of time suggests that the amino sugar levels roughly mirror an apparent biologic steady state between production and degradation of microbe‐derived materials.…”
Section: Basic Mass Relations In Microorganisms and In Soilmentioning
confidence: 99%
“…Prior studies showed that the total content of soil amino sugar‐N in most instances significantly exceeded the total amount of soil microbial biomass‐N (Appuhn & Joergensen, ; Joergensen, ; Joergensen, Mäder, & Fließbach, ). In a chronosequence of prolonged rice paddy management, the concentration of nitrogen in soil amino sugars exceeded the nitrogen content in living biomass by a factor of 2 in plots with continuous cultivation of over 190–2,000 years (Roth et al, ). The constancy of this factor over such a long period of time suggests that the amino sugar levels roughly mirror an apparent biologic steady state between production and degradation of microbe‐derived materials.…”
Section: Basic Mass Relations In Microorganisms and In Soilmentioning
confidence: 99%
“…It was not possible to find any soil older than 700 years not used for rice cultivation. Traditional paddy management in the region is a rotation with rice grown during the wet season, followed by wheat or another upland crop during the dry season (Fan et al, 2005;Roth et al, 2011). We cannot assume a constant management at all the sites during the 2000 years of paddy soil development.…”
Section: Study Areamentioning
confidence: 99%
“…Thus, frequent inundation leads to reduced rates of OM decomposition (Sahrawat, 2004(Sahrawat, , 2005, which may result in increases in OM storage (Cheng et al, 2009;Kögel-Knabner et al, 2010). Most OM storage under paddy management is restricted to the puddled layer Chen et al, 2011;Kalbitz et al, 2013;Roth et al, 2011;Wissing et al, 2011). The paddy-specific dense plow pan prevents OM from entering deeper soil layers, likely due to less deep rooting and diminished vertical water fluxes Lennartz, 2006, 2007;Kalbitz et al, 2013).…”
mentioning
confidence: 95%